Reinterpreting Islamic Inheritance Law For SDGs: A Comparative Analysis of Ibn Kathir and Amina Wadud on Gender Justice - Fuad Fansuri; Mursalim; Miftahul Ramadhani (Profetika: Jurnal Studi Islam, 2024)
Objective: This study examines the interpretation of QS. Al-Nisa (4): 11 relates to the division of inheritance between men and women by Ibn Katsir as a classical mufasir and Amina Wadud as a contemporary thinker. The purpose of the study is to explore the differences in the interpretation methodologies of the two, identify the factors that influence these differences, and assess their relevance to gender justice within the framework of the Sustainable Development Goals (SDGs), especially in the aspect of gender equality (SDG 5). Theoretical framework: The theoretical framework of this research refers to the hermeneutics of interpretation, with a focus on text and context. Literature Review: The literature analyzed includes Tafsir Al-Qur'an Al-Adzim by Ibn Katsir and Qur'an and Woman by Amina Wadud, as well as supporting sources that discuss Islamic inheritance law and gender justice issues. Methods: The research method is qualitative with a comparative-analytical approach. The data were systematically analyzed through three stages: methodological differences identification, relevance evaluation, and synthesis of findings. Results: The results of the study show that Ibn Katsir used a textual approach based on asbabun nuzul and the social context of the 7th-century Arab society. He emphasized the 2:1 division of inheritance as a fixed provision that reflects justice based on men's financial responsibility. In contrast, Amina Wadud adopts a contextual approach that considers the dynamics of women's roles in the modern era. He sees the rule as a flexible principle that can be adapted to the specific needs of the family, reflecting justice based on the actual contribution of the heirs. Implications: This research makes a new contribution by integrating classical and contemporary approaches to understanding the Qur'anic text in an adaptive manner to social change. The implication is that it supports a more inclusive dialogue to achieve gender equality and justice in Islamic inheritance law. Novelty: The uniqueness of this study is to enrich the discourse of Islamic law in supporting the achievement of the SDGs, especially in the aspects of social justice and women's empowerment.